Institutional Arrangements for Religion in Kosovo - Mehmedi, Jeton (Context: Journal of Interdisciplinary Studies, 2022)
Given the experience of war, the major challenge for post-war Kosovo has been to create an environment where different religious and ethnic groups can re-negotiate their differences and live in harmony with each other. Religion has been central to public discussion and contestation over the past decade. To minimize the role of religion and so fend off potential incidents, the international community put in place a strong secular system. This secular model has not been satisfied with the separation of state and religion, however, seeking rather a separation of society from religion to the point of marginalizing the latter and relegating it to purely private matters.